Kajian Kualitas Lingkungan Fisik-Kimia Akibat Pengoperasian Pembangkit Listrik Tenaga Surya Terpusat Di Desa Oelpuah Kecamatan Kupang Tengah Kabupaten Kupang - Micklon Edison Nakmofa; Johanis N Kallau; Adrianus Amheka (Bumi Lestari Journal of Environment, 2018)
The utilization of renewable electric power plants (non-fossil) in friendly environment needs to be done by using of solar energy for electricity generation. PT. LEN Industry built solar power Plant on Oelpuah Village, Kupang Tengah Subdistrict, Kupang Regency, with a total capacity of 5 megawatts Peak, which currently operates and the biggest Solar Power Plant in Indonesian. As a result of the operation of these solar power, it can be expected to have environmental impacts. The purpose of this study was to determine the impact of Physical Chemistry like air quality, water quality and noise, inside and outside of solar power plant operation. The results showed, because of PLTS Operation, it has an impact to physical chemistry environmental quality, but the impaCT STILL below the threshold of environmental quality standards.